اسلام اورہندومت میں احترام انسانیت ایک تقابلی جائزہ: Respect for Humanity in Islam and Hinduism A Comparative Review - Aslam , Imran; Asdullah, Prof. Dr Sajid (Al-Amīr Research Journal for Islamic Studies, 2022)
Every person in the world is respectable because he is a human being. All religions of the world have taught respect for humanity. It will not be wrong if we say that respect is the common heritage of humanity living in the world. Mutual respect is the secret and distinction of the development of nations. How many nations and cultures became enviable simply because they respected each other? In the present era, the dignity of humanity is being trampled everywhere. The murder market is hot everywhere. The standards of human respect are changing, sincerity, truth, human equality, and values ​​are being replaced by deceit, greed, envy, and selfishness. And it is done according to the resources. Man is the best of creation and legitimate respect and honor is his basic right. Therefore, no one can see his self-respect being undermined. That’s why it has become very important to bring up topics like respect for humanity and explain the position and status of human beings in the light of religious books so that the respect and dignity of human beings are being trampled underfoot today, people should be made aware of the true status and status of human beings should be informed so that the importance of human blood can be estimated. An attempt will be made in this paper to present a comparative review regarding the respect and reverence that human has for Islam and Hinduism. Keywords: Respect for Humanity, Superior to all creatures, Religion, Islam, Hinduism, Respect, Self-respect